Impairment in work and activities of daily life in patients with psoriasis: results of the prospective BioCAPTURE registry - Tamara W. van Hal; Juul M. P. A. van den Reek; Mark H. Wenink; Marisol E. Otero; Paul M. Ossenkoppele; Marcellus D. Njoo; Annet Oostveen; Bas Peters; Milan Tjioe; Else N. Kop; John E. M. Körver; Sharon R. P. Dodemont; et al. (Taylor & Francis Group, 2024)
AbstractBackground: Little is known about the extent of impairments in work and activities of daily life (ADL) in patients with psoriasis, and the influence of contextual factors such as disease-related characteristics and treatment. Therefore, this study aimed to assess these impairments in patients with psoriasis who started using biologicals/small molecule inhibitors.Methods: Using data from the prospective BioCAPTURE registry, we collected patient, disease, and treatment parameters, as well as work/ADL impairments at baseline, 6 and 12 months. Changes in impairment parameters and correlations between impairment and patient/disease characteristics were assessed using generalized estimating equations.Results: We included 194 patients in our analysis. After biological initiation, disease activity decreased significantly (PASI 11.2 at baseline versus 3.9 at 12 months, p < 0.001). Work-for-pay in this cohort was lower than in the Dutch general population (53% versus 67%, p = 0.01). In patients who had work-for-pay, presenteeism improved over time (5% at baseline versus 0% at 12 months, p = 0.04). Up to half of the patients reported impairments in ADL, which did not change over time. Associations between impairments and contextual factors varied, but all impairments were associated with worse mental/physical general functioning.Conclusion: Patients with psoriasis using biologicals are less likely to have work-for-pay. Treatment improves the work productivity of employed patients, but we were unable to detect changes in ADL performance.